2015
DOI: 10.1016/j.quageo.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of paired quartz OSL and feldspar post-IR IRSL dose distributions in poorly bleached fluvial sediments from South Africa

Abstract: A comparative study using quartz optically stimulated luminescence (OSL) and feldspar post-infrared infrared stimulated luminescence (post-IR IRSL) was undertaken on Quaternary fluvial sediments from an unnamed tributary of the Moopetsi River in South Africa. The aim is to assess whether the post-IR IRSL signal can be used to date incompletely bleached sediments. Several post-IR IRSL signals using varying stimulation and preheat temperatures were investigated; of these the post-IR IRSL225 signal was deemed mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 15 publications
2
46
0
2
Order By: Relevance
“…This argument is based on the widely-observed differential bleaching rates of quartz and feldspar signals (e.g. Godfrey-Smith et al, 1988;Thomsen et al, 2008;Buylaert et al, 2012;Murray et al, 2012;Sugisaki et al, 2015;Colarossi et al, 2015) when exposed to a daylight spectrum, and helps to quantitatively address one of the main uncertainties in the application of OSL to dating.…”
Section: K-rich Feldsparmentioning
confidence: 99%
“…This argument is based on the widely-observed differential bleaching rates of quartz and feldspar signals (e.g. Godfrey-Smith et al, 1988;Thomsen et al, 2008;Buylaert et al, 2012;Murray et al, 2012;Sugisaki et al, 2015;Colarossi et al, 2015) when exposed to a daylight spectrum, and helps to quantitatively address one of the main uncertainties in the application of OSL to dating.…”
Section: K-rich Feldsparmentioning
confidence: 99%
“… and references therein; Colarossi et al . ). Alternatively, several models have been proposed to correct faded ages (e.g.…”
mentioning
confidence: 97%
“…Several studies have shown that the quartz OSL signal resets faster than the K‐feldspar IR 50 signal and that the IR 50 signal, in turn, bleaches more rapidly than the elevated temperature pIRIR signals (e.g. Godfrey‐Smith et al ., ; Thomsen et al ., ; Murray et al ., ; Kars et al ., ; Colarossi et al ., ; Möller and Murray, ; Sugisaki et al ., ). Based on this, Murray et al .…”
Section: Discussionmentioning
confidence: 99%